Novel, diverse RNA viruses from Mediterranean isolates of the phytopathogenic fungus, Rosellinia necatrix: insights into evolutionary biology of fungal viruses - Arjona‐Lopez, Juan Manuel; Telengech, Paul; Jamal, Atif; Hisano, Sakae; Kondo, Hideki; Yelin, Mery Dafny; Arjona‐Girona, Isabel; Kanematsu, Satoko; Lopez‐Herrera, Carlos José; Suzuki, Nobuhiro (Environmental microbiology, 2018)
Summary To reveal mycovirus diversity, we conducted a search of as‐yet‐unexplored Mediterranean isolates of the phytopathogenic ascomycete Rosellinia necatrix for virus infections. Of seventy‐nine, eleven fungal isolates tested RNA virus‐positive, with many showing coinfections, indicating a virus incidence of 14%, which is slightly lower than that (approximately 20%) previously reported for extensive surveys of over 1000 Japanese R. necatrix isolates. All viral sequences were fully or partially characterized by Sanger and next‐generation sequencing. These sequences appear to represent isolates of various new species spanning at least 6 established or previously proposed families such as Partiti‐, Hypo‐, Megabirna‐, Yado‐kari‐, Fusagra‐ and Fusarividae, as well as a newly proposed family, Megatotiviridae. This observation greatly expands the diversity of R. necatrix viruses, because no hypo‐, fusagra‐ or megatotiviruses were previously reported from R. necatrix. The sequence analyses showed a rare horizontal gene transfer event of the 2A‐like protease domain between a dsRNA (phlegivirus) and a positive‐sense, single‐stranded RNA virus (hypovirus). Moreover, many of the newly detected viruses showed the closest relation to viruses reported from fungi other than R. necatrix, such as Fusarium spp., which are sympatric to R. necatrix. These combined results imply horizontal virus transfer between these soil‐inhabitant fungi.